1995
DOI: 10.1063/1.468792
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale microsegregation in polyacrylamide gels (spinodal gels)

Abstract: Exceptionally large pore sizes have recently been reported for polyacrylamide gels grown in the presence of polyethylene glycol. We present small angle static light scattering measurements performed during the evolution of this peculiar gelation process. We give evidence that the large pores are generated by a microsegregation process caused by the competition between gelation and a phase separation of the polymers solution. The separation occurs via spinodal decomposition, and the size of the pores is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 27 publications
2
39
1
Order By: Relevance
“…Therefore the above scenario for gelation does not apply to our system. As mentioned in the Introduction gelation can also result from a fluid-fluid phase separation which is arrested at some intermediate stage either by a sol-gel transition [13,27] or by a glass transition [14,15] leaving the system in a state of microphase separation. A thermodynamic model for this mode of gelation was presented by Frank and Keller [28] and a kinetic model by Sciortino et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the above scenario for gelation does not apply to our system. As mentioned in the Introduction gelation can also result from a fluid-fluid phase separation which is arrested at some intermediate stage either by a sol-gel transition [13,27] or by a glass transition [14,15] leaving the system in a state of microphase separation. A thermodynamic model for this mode of gelation was presented by Frank and Keller [28] and a kinetic model by Sciortino et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…0.0012 nm À1 . This q À3 behavior observed in the MC solution suggests that the fractal dimension of the boundary surface of the pores in this gel is equal to 3 and has been observed in highly porous materials, such as lignite coals, [39] polymer gelations [35] and colloidal solutions. [40] To determine the kinetics of the phase-separation process, we constructed a semilogarithmic plot of scattering intensity versus time (s) at different q values, shown in Figure 4 for 5 g Á L À1 MC in the presence of 5% (w/w) NaCl after a temperature jump from 0 8C to 49 8C and isothermal annealing at 49 8C.…”
Section: Resultsmentioning
confidence: 95%
“…Similar results were obtained for the samples quenched to 48, 50 and 51 8C (not shown here). Asnagi et al [35] used the SALS technique to study the gelation process in polyacrylamide solutions in the presence of polyethylene glycol (PEG). They observed that the phase separation occurs via SD, and two maxima were observed for some analyzed compositions with lower PEG concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Among the reasons for the formation of structural heterogeneities in the growing networks, the spontaneous tendency of monomers, cross-linkers and solvent to separate during the polymerisation into uniform clusters in different spatial regions is a major factor (Kloosterboer, 1998;Anseth et al, 1996). Such segregation is defined as spinodal decomposition (Asnaghi et al, 1995), it generates local environments composed of molecules with 0956-5663/$ -see front matter © 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.bios.2010.02.015 similar properties (hydrophobicity and density) and ultimately results in different microgelation environments in the same polymerisation reaction and thereby gives rise to heterogeneities.…”
Section: Introductionmentioning
confidence: 99%